MaineCare—A Provider Prospective - Steele, Erik (Maine Policy Review, 2007)
Dr. Erik Steele in this commentary discusses MaineCare (Maine’s Medicaid program) from a provider’s perspective. He suggests that delays and problems in the state’s reimbursement to providers have led to doubts about the state’s credibility both as a payer and as a health care systems change leader.